Breastfeeding a small for gestational age infant, complicated by maternal gestational diabetes: a case report - Alexandra D. George; Melvin C. L. Gay; Mary E. Wlodek; Donna T. Geddes (BMC, 2019)
Abstract Background Small for gestational age (SGA) infants are those born small for their gestational age, with weight below the 10th percentile. Not only do SGA infants suffer growth issues after birth, they have elevated risk for the development of metabolic and cardiovascular diseases later in life. Current research has suggested that in cases of SGA infants, maternal milk and breastfeeding are not affected. Case summary The mother of an SGA infant was diagnosed with placental insufficiency and Gestational Diabetes Mellitus (GDM) during her pregnancy. The infant was born term, at 38 weeks 3 days, and SGA. The mother had a low milk supply and her milk composition differed from reference values such that the daily infant intake provided less than 50% of the required energy intake at 3 months. Conclusion In cases of SGA and/or GDM, maternal milk quality and quantity may be compromised. This requires follow-up in order to reduce the disease risk for SGA infants and the corresponding public health implications.